Design and fabrication of a bioreactor for the proliferation of mesenchymal stem cells - De los Santos, Morelia; Castruita Avila, Laura; Zuñiga Aguilar, Esmeralda; Ramirez Fernandez, Odin (Cultura Científica y Tecnológica, 2023)
Currently, the number of organ donors is low and there are different methods to deal with this situation, including cell cultures, decellularization and bioreactors, which play an important role in helping the required processes to be carried out in a faster and more optimized way. The objective of this work is to make the cell proliferation process efficient using a bioreactor as an alternative, in which flow simulations can be made to previously analyze how it works. The radial flow hydraulic circuit was designed and simulated in SOLIDWORKS solving Navier-Stokes equations to verify that we have a non-turbulent laminar flow and simulate cell detachment without damaging the cell matrices. The design was printed with additive printing techniques, using photosensitive resin. Bioreactors also play a part in tissue engineering, as they allow for changes that can be monitored and reproduced in particular environmental factors. This article shows the successful design of a bioreactor to proliferate mesenchymal stem cells printed and subjected to simulations, whose results lead to the conclusion that there is non-turbulent laminar flow in the behavior of the system without subjecting the cells to a possible stress that causes damage.